The Effect of Removal of Baggage Facilities on Customer Satisfaction at Wings Air - Satriyadin faisal; Sri Ernawati Zunaidin (Profesional Muda Cendekia Publishing, 2021)
Satisfying consumer needs is the desire of every company. Apart from being an important factor for the company's survival, satisfying the needs of consumers can increase its advantage over the competition. Consumers who are satisfied with products and services tend to buy back products and reuse services when the same needs reappear at a later date. This study aims to determine the effect of removal of baggage facilities on customer satisfaction on Air Wings Airline. This research uses a quantitative approach with a survey method. This study uses a quantitative approach with a survey method, while this type of research is categorized as a causal research. The population in this study are consumers who have used air flight services using wing air, the number of samples taken in this study were 50 respondents with the sampling used in this study was purposive sampling. The research instrument used a questionnaire with a Likert scale. Data analysis used simple linear regression, partial test with t test. To test the effect between variables using SPSS (Statistical Service Product Solutions) version 23.00. The results showed that the elimination of baggage facilities had a positive and significant effect on customer satisfaction on the Air Wings airline